2018
DOI: 10.4236/crcm.2018.73017
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Right-Sided Infective Endocarditis—An Infected Right Ventricular Myxoma Masquerading as “Tricuspid Vegetation”—A Case Report

Abstract: Aim: To report a case of right ventricular myxoma prolapsing through the tricuspid valve with an attachment of vegetation in a 3-year-old male child. Introduction: Right-sided endocarditis commonly involves the tricuspid valve. Low pressure and low oxygen saturation in the right sided cardiac chambers protect the tricuspid and pulmonary valves from being subjected to excessive strained and damage occurs from injected particulate matter, contaminated venous lines and drug solutions causing endocarditis. RV (rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…1,2 However; it can be associated with any other intracardiac oscillatory mass or vibratory structure, 3,4 or even with native valve regurgitation, as was reported by Goyal (Goyal et al 2018 The tiger stripes sign is not specific to a certain valvular. A case reported by Muthiah (Muthiah 2018) showed the appearance of tiger stripes at the tricuspid valve due to the oscillating mass across the valve. 7 as well as Sahu's case (Sahu et al 2016) showed the tiger stripes within the tricuspid regurgitation arising probably due to abnormal septal tricuspid leaflet oscillatory motion with the jet of TR.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However; it can be associated with any other intracardiac oscillatory mass or vibratory structure, 3,4 or even with native valve regurgitation, as was reported by Goyal (Goyal et al 2018 The tiger stripes sign is not specific to a certain valvular. A case reported by Muthiah (Muthiah 2018) showed the appearance of tiger stripes at the tricuspid valve due to the oscillating mass across the valve. 7 as well as Sahu's case (Sahu et al 2016) showed the tiger stripes within the tricuspid regurgitation arising probably due to abnormal septal tricuspid leaflet oscillatory motion with the jet of TR.…”
Section: Discussionmentioning
confidence: 99%